2016
DOI: 10.1073/pnas.1612132113
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlate of the construction of sentence meaning

Abstract: The neural processes that underlie your ability to read and understand this sentence are unknown. Sentence comprehension occurs very rapidly, and can only be understood at a mechanistic level by discovering the precise sequence of underlying computational and neural events. However, we have no continuous and online neural measure of sentence processing with high spatial and temporal resolution. Here we report just such a measure: intracranial recordings from the surface of the human brain show that neural acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
223
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(264 citation statements)
references
References 82 publications
40
223
1
Order By: Relevance
“…This effect flipped for words 6-10 in TP and aSTS, where activity continued to increase in the sentence condition and became significantly higher in sentences than word lists. Those findings are congruent with a previous report of a systematic increase in intracranial high-gamma activity across successive words in sentences but not word lists (21) and suggest that working memory demands may saturate after five unrelated words.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This effect flipped for words 6-10 in TP and aSTS, where activity continued to increase in the sentence condition and became significantly higher in sentences than word lists. Those findings are congruent with a previous report of a systematic increase in intracranial high-gamma activity across successive words in sentences but not word lists (21) and suggest that working memory demands may saturate after five unrelated words.…”
Section: Resultssupporting
confidence: 91%
“…With the high temporal resolution afforded by intracranial recordings, phrase structure indeed appears as a major determinant of the dynamic profile of brain activity in language areas. A recent study monitored high-gamma intracranial signals during sentence processing and, after averaging across a variety of sentence structures, concluded that high-gamma activity increases monotonically with the number of words in a sentence (21). The present results suggest that this is only true on average: When time-locking on the onset and offset of phrase structures, we found that this overall increase, in fact, was frequently punctuated by sudden decreases in activity that occur at phrase boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hierarchy, as well as the divergence of neural responses observed here, is additionally consistent with previously proposed linguistic hierarchies: low-level regions (A1+) represent phonemes (32,33), syllables (34), and pseudowords (35), while medium-level regions (areas along A1+ to STS) represent sentences (36,37). At the top of the hierarchy, high-level regions (bilateral TPJ, precuneus, and medial prefrontal cortex) can integrate words and sentences into a meaningful, coherent whole narrative (5,15,(38)(39)(40).…”
Section: Discussionsupporting
confidence: 92%
“…In intracranial recording, neurological patients volunteer to perform a task while electrodes, implanted in their brains for clinical reasons, continuously monitor neural activity. It offers the most direct measure possible of neural activity in humans, and as such is attractive to researchers from across many disciplines (Fedorenko et al, 2016;Martin et al, 2016;Rutishauser et al, 2006). Recordings can be made either from the cortical surface (referred to here as ECoG, short for electrocorticogram) or from beneath the cortical surface (referred to here as depth recordings).…”
Section: Introductionmentioning
confidence: 99%